Faktor-Faktor Yang Mempengaruhi Erc Pada Perusahaan Manufaktur - Yohana Adelia Della Ros, Ardiansyah (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to examine the effect of firm size, audit committee, capital structure, and liquidity on earnings response coefficient manufacturing companies listed on the Indonesia Stock Exchange during 2016-2018. This study uses 75 manufacturing companies that have been selected through a purposive sampling method with a total of 184 data for three years. Multiple regression analysis is a model to proceed the whole data by using the spss program (Statistical Product and Service Solution) version 25 and Microsoft Excel. The study can not proof the two variables, the firm size and audit positively affect ERC. Capital structure has a negative and not significant and also liquidity has a positive tendency, but not significant. In order to that factors such as firm size, audit committee, capital structure and liquidity can be some factors which affect to.